1968
DOI: 10.1002/pol.1968.160060517
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of cold‐drawn nylon 66

Abstract: SynopsisA nylon 66 composed of uniformly sized spherulites approximately 50 p in diameter was examined before and after cold drawing by light and electron microscopy of thin sections and by low-angle x-ray diffraction. Spherulites retained their identity through drawing, but the spherulites elongated less than the bulk specimen indicating that relative motion of spherulites must have occurred. The observation of dilations (0.3 p long) at interspherulitic boundaries support this contention. The thin-section ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

1970
1970
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 5 publications
0
9
1
Order By: Relevance
“…Occasionally there are some indications of fibrous features within the electron micrographs (see Fig. 3), but unlike Hess et al [28], Crystal and Hansen [27], Prevorsek et al [16,29], and Geigenfeind and Owen [30] we cannot obtain clear evidence for a microfibrillar structure from our investigations. The appearance of a structure similar to that of the cold-drawn bristles was revealed in commercial nylon 6 fibres (Fig.…”
Section: Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…Occasionally there are some indications of fibrous features within the electron micrographs (see Fig. 3), but unlike Hess et al [28], Crystal and Hansen [27], Prevorsek et al [16,29], and Geigenfeind and Owen [30] we cannot obtain clear evidence for a microfibrillar structure from our investigations. The appearance of a structure similar to that of the cold-drawn bristles was revealed in commercial nylon 6 fibres (Fig.…”
Section: Resultscontrasting
confidence: 75%
“…Furthermore, concerning the morphological characteristics of drawn material, attempts have been made using nylon 6 and nylon 66 in particular, to reveal the crystalline-amorphous microstructure by electron microscopy (EM). Rusnock and Hansen [26] and Crystal and Hansen [27] reproduced deformed spherulites of nylon 66 bristles by ultra-thin sections, which were stained with phosphotungstic acid (PTA). Previously, in a similar way Hess et al [28] had identified a structural periodicity within dispersed fibrils of commercial nylon 6 filaments.…”
Section: Introductionmentioning
confidence: 99%
“…Lamellar sheaves in nylon 6 have been well established for the crystallization from solution [11,[28][29][30][31]. Figure 5 shows a sheaf in a stained thin film with the constituent crystalline lamellae (having thicknesses of approximately 4.5 nm) being very evident.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning other crystalline polymers, staining techniques have rarely been used up to now (see [7]). K 75 Phosphotungstic acid (PTA) which is well known for the negative staining of proteins, seems to be a suitable reagent for all polyamids according to the early investigations by Hess et al [8] on dispersed fibrils from nylon 6 fibres, by Spit [9,10] on solutiongrown nylon 6 films, and by Crystal and Hansen [11] on sections from nylon 66 bulk material. For investigations on the bulk it proved, however, to be very difficult in general to combine the requirements of high efficiency staining with appropriate sectioning properties of the material so as to produce suitable ultrathin sections.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, extensive small-angle x-ray scattering observations on drawn. polyethylene and polypropylene have been reported by Corneliussen and I'eterlin [4,5] and Balta-Calleja and Peterlin (1,2,3]. Notably, the observed periodicity along the draw axis, as well as the variation of the periodicity with drawing temperature, were accommodated by the I'eterlin model.…”
Section: Introductionmentioning
confidence: 57%